2015 Computing in Cardiology Conference (CinC) 2015
DOI: 10.1109/cic.2015.7408577
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and consistent automatic seismocardiogram annotation without concurrent ECG

Abstract: Seismocardiography (SCG) is the measurement of vibrations in the sternum caused by the beating of the heart. Precise cardiac mechanical timings that can only be obtained from SCG are critically dependent on accurate identification of fiducial points.So far, SCG annotation has relied on concurrent ECG measurements. We have designed an algorithm capable of annotating SCG without the use any other concurrent measurement. We subjected 18 participants to graded lower body negative pressure. We collected ECG and SCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This indicates a strong influence of the presence of valvular heart disease on HRV indices, except AVNN (mean interbeat interval) and VLF, which was in line with [29,30]. The similarities between the results of the HRV analysis in patients with VHD in our study and those reported in [29] prove that the HRV indices obtained from seismocardiograms are valid for patients with aortic stenosis and also for other VHD [14,31].…”
Section: Discussionsupporting
confidence: 86%
“…This indicates a strong influence of the presence of valvular heart disease on HRV indices, except AVNN (mean interbeat interval) and VLF, which was in line with [29,30]. The similarities between the results of the HRV analysis in patients with VHD in our study and those reported in [29] prove that the HRV indices obtained from seismocardiograms are valid for patients with aortic stenosis and also for other VHD [14,31].…”
Section: Discussionsupporting
confidence: 86%
“…Over the years, various algorithms have been employed for HRV detection from ECG, with many based on R-peak detection in QRS complexes [27]. Laurin et al [28] demonstrated the reliability of HRV indices derived from SCG signals, and Tadi et al [29] confirmed a strong association between HRV indices derived from ECG and SCG. Beyond traditional ECG applications, MCG signals have proven effective in classifying cardiovascular anomalies through smartphones [1], [30], estimating respiratory rate (RR) [12], [31], determining tidal volume alongside ECG from SCG [32], estimating cardiac time intervals from SCG [33], real-time cardiovascular disease detection for drivers [34], among other applications.…”
Section: Introductionmentioning
confidence: 99%
“…With a few exceptions, these methods have been limited to single-point measurements on the chest surface. While automatic annotation algorithms have been developed [3,4], and published studies demonstrate potential uses for clinical applications [5][6][7][8][9], SCG has so far largely remains confined to scientific laboratories. This is in part due to the lack of physiological and physical understanding of the processes that underlie the phenomena, causing lasting uncertainties as to the exact interpretation of the signal's peaks and valleys, as well as some variability in accelerometer placement.…”
Section: Introductionmentioning
confidence: 99%